Engeström’s activity theory as a tool to analyse online resources embedding academic literacies - Behrend, Monica (Journal of Academic Language and Learning, 2014)
Engeström’s third generation activity theory, situated within sociocultural theory, can be used to analyse complexities within and surrounding academic activities, such as writing assignments or using online resources. This theory provides a tool to analyse how individual or groups use mediating artefacts (for example, an online writing resource) to achieve a specific object and outcome. This theory also provides a framework to analyse sociocultural influences of rules and norms, community and division of labour in the same activity system. Activity theory analysis describes these components and examines their interrelationship to identify affordances and contradictions within the system. As an activity system is not independent of other related activity systems, an analysis also considers co-existing related activity systems. Any contradictions can then be potentially addressed, transforming the activity and achieving improved outcomes. Activity theory can be used in conjunction with other research paradigms, such as action research. Whilst such a combination of paradigms can be viewed as controversial, some researchers use both activity theory and action research. This paper illustrates the value of using activity theory with action research to examine two networked academic activity systems –namely: 1) writing assignments, and 2) providing Academic Language and Learning (ALL) support online – which were implemented over three action research cycles. The analysis of the first action research cycle highlights the potential of activity theory to identify how contradictions lead to change for the activity and the stakeholders in the activity – both academics and students.